Analysis of Opportunities and Challenges of Blockchain Technology in the Islamic Banking Industry (Case Study on the Use of Smart Contracts) - farhan, muhammad; Imsar, Imsar; Dharma, Budi (Penerbit Goodwood, 2024)
Purpose: This research concludes that, with a strategic and collaborative approach, blockchain technology can be an effective tool for transforming the Islamic banking industry. Methodology: This study uses qualitative methods with literature analysis from 19 journals, one book, and three websites to explore how this technology can be applied in risk management, asset tracking, and interbank transactions. Results: The research results reveal that this technology can reduce fraud, manipulation, and cyberattacks, as well as increase customer and sharia authority trust through transaction transparency. However, there are major challenges to overcome, such as immature regulatory aspects, the need for a strong infrastructure, and a lack of understanding of this technology among customers. This study also emphasizes the importance of collaboration between Islamic banking, regulators, and other stakeholders to maximize the potential of blockchain technology. Limitations: Case studies on the use of smart contracts in the Sharia banking industry show that this technology can increase efficiency and Sharia compliance, reduce administration costs, and simplify transactions. Contribution: This study describes the role of blockchain in the sukuk issuance process. Blockchain technology, which is known for its decentralization, transparency, and security characteristics, has great potential to increase efficiency and transparency in Sharia banking operations.